Am I getting my point across? Microstructure of English classroom discourses by Acehnese teachers - Meta Keumala; Dohra Fitrisia; Iskandar Abdul Samad; Sofyan Abdul Gani (Universitas Syiah Kuala, 2022)
For English teaching practice, productive talks that spur students’ comprehension, creativity, and problem-solving ability are vital. This research aimed at finding out the spoken discourse based on six phases of microstructure in English classrooms. The data were obtained recordings and observations of two English teachers, chosen through purposive sampling, from Islamic senior high schools in Aceh. The data were concerned with the lexical density or the ratio of content to grammatical or function words within a clause. They were analyzed through thematic analysis which consists of five steps: data familiarization, code generation, theme search, themes revision, and theme definition. It was found that the total lexical density obtained by the first teacher in Class A was 63.66% and in class, B was 66.52%, while the second teacher in Class A was 71. 74% and in Class B was 68.12%. The second teacher 2 in Class A had a higher lexical density than the first teacher even though both of them are considered to produce a high lexical density of around 60-70%. The formality of spoken discourse of the two teachers shows that the first teacher produced 172.5 while the second teacher produced 184. It means that the second teacher's spoken discourse was more formal than the first teacher’s discourse. To analyze the utterances of teachers and to find the density of language used in the classrooms during the teaching and learning process is important because they implicitly inform whether the language used is understandable for the students or not.